DESA SEHAT DALAM PENCEGAHAN HIV/AIDS PADA REMAJA PESISIR BERBASIS VIRTUAL REALITY - Rusli Taher; Nurhikmah, Nurhikmah; Rusman K; Erwin, Erwin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aimed to improve the knowledge and awareness of adolescent groups in Tupabbiring Village, Bontoa District, Maros Regency regarding the prevention of HIV/AIDS using Virtual Reality-based learning. Conducted by lecturers and students of STIKES Graha Edukasi Makassar, the activity involved preparation, implementation of health education, and evaluation stages. The health education was delivered through theory and practical sessions on HIV/AIDS prevention using Virtual Reality media. Evaluation through pre-test and post-test using SPSS showed an increase in participants’ knowledge from 51.36% to 93.03%. This activity demonstrates the effectiveness of Virtual Reality-based education in improving health knowledge and awareness among coastal adolescents with limited access to health services.